Contextual Learning Innovations in Islamic Education Textbooks at Muhammadiyah Elementary School Grade VI - Ilham Mundzir (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2022)
This article aims to analyze the instructional methods used in textbooks to increase understanding of Islam at the primary education level in Indonesia, namely Islamic Education for 6th grade of Muhammadiyah Elementary School published by Muhammadiyah Executive Board of Primary and Secondary Education. This textbook research was conducted using a qualitative method, with a content-analysis approach to the instructional methods used in the book. The results of the study showed that this Al-Islam Education textbook innovated by applying contextual teaching and learning (CTL) methods. In the end, this Islamic Education textbook published by Educational Council of Central Board of Muhammadiyah can serve as a good example of the openness of Islamic educational institutions to apply CTL-based instructional methods in Islamic education, in order to increase students' understanding and practice of Islam while at the same time improving the quality of Islamic religious education in Indonesia in general.